Wastewater treatment and Mycoremediation by P. ostreatus mycelium - Bhatnagar, A.; Tamboli, E.; Mishra, A. (IOP Publishing Ltd, 2021)
Wastewater from industries contains a considerable amount of chemicals and is characterized by high biological oxygen demand (BOD), heavy metals, intense color and are thus toxic to the environment. White-rot fungi such as Oyster mushrooms are comprised of high biomass and various degradative enzymes that add to another dimension of use, such as mycoremediation. The mushroom was maintained in vitro in mycelial form. Remazol Brilliant Blue R (RBBR), Methyl Red (M.R.), and Malachite Green (M.G.) dyes, which are recalcitrant dyes that are often used for the preparation of many polymeric dyes, and textile dyeing, were used to test the decolorization potential of natural isolates of oyster mushroom. Mycelium was grown in the presence of RBBR, MR, and M.G. at a concentration of 100μM. It was found to decolorize more than 70%, 95%, and 80% of RBBR, MR, and M.G. dye, respectively, within 6 days. Mushroom mycelium was also tested for its lead tolerance and heavy metal biosorption potential. Lead tolerance was studied up to 500mg/L, which shows species′ latent growth with fungal morphology changes. Biosorption ability was observed by the use of Inductively Coupled Plasma spectrometry, which shows lowered concentrations of heavy metals (Pb, Cr, Ni) after 5 days of mycelial growth in the presence of these metals. The isolated strain was also found to have significant decolorizing and degrading potential for synthetic dyes and phenolic compounds in industrial effluents. This study focuses on edible oyster mushrooms′ ability to develop environmentally less aggressive processes in the treatment of industrial effluents.
Keywords: dye decolorization; fungi; heavy metal biosorption; mycoremediation; oyster mushrooms; wastewater treatment